Emerging Technological Trends for Enhancing Healthcare Access in Remote Areas (Journal of Science & Technology, 2021)
Access to quality healthcare is a fundamental human right, yet many remote areas around the world lack adequate healthcare services. Emerging technologies offer promising solutions to bridge this gap and improve healthcare access in remote areas. This paper explores the latest technological trends and innovations that are transforming healthcare delivery in remote areas. We discuss the role of telemedicine, mobile health (mHealth) applications, wearable devices, Internet of Things (IoT) devices, and artificial intelligence (AI) in enhancing healthcare access. Additionally, we highlight the challenges and opportunities associated with implementing these technologies in remote healthcare settings. By understanding these emerging trends, policymakers, healthcare providers, and technology developers can collaborate to create more accessible and efficient healthcare systems for remote populations.